Copper immobilized ferromagnetic nanoparticle triazine dendrimer (FMNP@TD–Cu(ii))-catalyzed regioselective synthesis of 1, 4-disubstituted 1, 2, 3-triazoles. (19th February 2016) - Bahrami, Kiumars; Sheikh Arabi, Mehdi
Abstract : The synthesis, characterisation and catalytic activity of FMNP@TD–Cu(ii ) for the synthesis of 1, 4-disubstituted 1, 2, 3-triazoles are reported. Abstract : A copper immobilized ferromagnetic nanoparticle triazine dendrimer (FMNP@TD–Cu(ii )) has been demonstrated for the first time as a recoverable and reusable heterogeneous nanocatalyst in the click synthesis of 1, 4-disubstituted 1, 2, 3-triazoles by a one-pot three component reaction of halides, sodium azides and alkynes under mild conditions. The catalyst is very easy to handle and is environmentally safe and economical. FMNP@TD–Cu(ii ) was characterized using transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), FT-IR and EDX methods.